Narthex - Ghosh, Ayan (2023)
View of the central hall of St. Thomas Church from the lobby. The chancel gates separate the hall from the lobby, also called the narthex. The purpose of the narthex was to allow those not eligible for admittance into the general congregation to partake of the service from a distance. The floor is covered in Minton tiles made in Staffordshire, England.